Numerical investigation of free convection boundary layer flow on a vertical surface with prescribed wall temperature and heat flux - Mohd Zuki Salleh,; Roslinda Mohd Nazar, (Penerbit ukm, 2008)

(untitled)
In this paper, the existing model first considered by Merkin (1985) for free convection boundary layer flow on a vertical surface with prescribed wall temperature (PWT) and prescribed heat flux (PHF) is investigated numerically. The transformed boundary layer equations are solved using an efficient numerical scheme known as the Keller-Box method. Numerical solutions are obtained for the skin friction coefficient, local heat transfer coefficient, wall temperature as well as the velocity and temperature profiles. The features of the flow and heat transfer characteristics for large range of values of the Prandtl number are analyzed and discussed. Comparisons with previous work by other method for the cases of Pr = 0.72, 1 and 7 show very good agreement. In addition, results for small (Pr << 1) and large (Pr >> 1) values of Prandtl number (Pr) are also presented